Performance of rc low encoding techniques for reducing coupling transitions - V, Shavali.; Sreerama Reddy G.M, Dr.; Ramana Reddy.P, Dr. (International Journal of Engineering and Technology, 2018)
RC Network has delay propagation by wire and dynamic power dissipation. Basically it can perform two encoding techniques. They are Firstly it will reduce more dynamic power dissipation and delay propagation of wire simultaneously. Its simulation results of coupling activity and switching activity is more when the input is in Toggle state on 8-bit and for 32-bit data buses It increases. To reduce dynamic power is bus and total propagation delay the encoding techniques is Introduced which reduces coupling Coupling transitions, Dynamic power. Secondly it will also reduce more total power consumption when Width of Bus and Length of Bits Increases Its coupling activity is Reduced Gradually when the Data moves for one state to another State and switching activity is Reduced